ANALISIS TINGKAT KEPUASAN PEMILIK PERUMAHAN TERHADAP FASILITAS DAN KUALITAS BANGUNAN PERUMAHAN MEGAH RESIDENCE KOTA BENGKULU MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) F (UNIB Press, 2024)
Abstract: The population growth rate in Indonesia is high if compares to other developing countries. The increase in population also increases the need for housing facilities. Homeowner satisfaction is an absolute thing for developers to pay attention to and fulfill, including satisfaction with housing facilities and quality. The purpose of this study is to measure the satisfaction level of homeowners and to find out the dominant factors that influence home owner satisfaction. The research method was carried out by distributing questionnaires to respondents in Megah Residence housing, then the data from the questionnaire results were processed and analyzed, included data validity test, data reliability test, and the importance of performance analysis. The results obtained show that the indicators that give satisfaction to homeowners from the facility variables are the outside appearance of the house (3.50), the size of the house (3.58), the layout (3.67), air circulation (3.58), the adequacy of the room get natural light (3.67), housing drainage (3.50), flood safe areas (3.75). Indicators that give home owner satisfaction from the variable of building quality are the roof of the house (3.67), the structure of the house (3.71), the full ceramic floor (3.83). The dominant factor that affects the satisfaction of homeowners is the design of the house (3,63). Based on impoerance performance analysis, these indicators provide satisfaction to the home owner and must be maintained by the developer